2021
DOI: 10.1111/bph.15629
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism by which atropine inhibits myopia: evidence against cholinergic hyperactivity and modulation of dopamine release

Abstract: Background and Purpose:The ability of the muscarinic-cholinergic antagonist atropine to inhibit myopia development in humans and animal models would suggest that cholinergic hyperactivity may underlie myopic growth. To test this, we investigated whether cholinergic agonists accelerate ocular growth rates in chickens. Furthermore, we investigated whether atropine alters ocular growth by down-stream modulation of dopamine levels, a mechanism postulated to underly its anti-myopic effects.Experimental Approach: Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 76 publications
1
20
1
Order By: Relevance
“…At this dose, atropine also blocked development of deprivation myopia completely [21]. An increase in dopamine release from the retina at the same dose of atropine was found by Thomson et al [22] but no changes were observed at lower doses (10 µg and 0.1 µg).…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…At this dose, atropine also blocked development of deprivation myopia completely [21]. An increase in dopamine release from the retina at the same dose of atropine was found by Thomson et al [22] but no changes were observed at lower doses (10 µg and 0.1 µg).…”
Section: Introductionsupporting
confidence: 76%
“…Dopamine was measured by mass spectrometry which interestingly showed a DOPAC to dopamine ratio in the vitreous of 150 to 300 while the ratio was about 10 in our HPLC measurements, or even lower in other studies [44,52]. Another difference was that Thomson et al [22] measured dopamine 1 h after injection while we measured after about 2 h. Tian et al [52] had stated that "The retinal DOPAC/ dopamine ratio, indicating the metabolic efficiency of dopamine, is correlated with ocular growth." Therefore, we also studied whether the DOPAC to dopamine ratios might achieve better correlations with choroidal thickness changes.…”
Section: Finding (1)-inhibition Of Atropine-induced Choroidal Thicken...contrasting
confidence: 65%
See 2 more Smart Citations
“…It was proven that retinal dopamine exerts a protective effect against myopic growth via a D2-like mechanism in both models [ 15 ]. More importantly, dopamine signaling seemed to play a role in the protective effect of time outdoors, increased illuminance and low-dose atropine [ 16 , 17 , 18 , 19 ], which suggests that the shared mechanism in the retina of the two models might have general clinical implications. Although dopamine signaling plays an important role in myopia development, it cannot fully explain the onset and progression of myopia, and its upstream and downstream pathways are not fully understood [ 20 ].…”
Section: Introductionmentioning
confidence: 99%